White Matter Language Pathways and Language Performance in Healthy Adults Across Ages - Houston, James; Allendorfer, Jane; Nenert, Rodolph; Goodman, Adam M.; Szaflarski, Jerzy P. (Frontiers in Neuroscience, 2019)
White matter pathways associated with language functions include the arcuate (AF), superior longitudinal (SLF), inferior longitudinal (ILF), inferior frontal-occipital (IFOF), and uncinate (UF) fasciculi. Using Tract Based Spatial Statistics (TBSS), we investigated if measurements of white matter integrity in these pathways correlate with linguistic performance. 228 healthy participants (126 female; 146 right-handed), ages 18 to 76, underwent 3.0 Tesla MR diffusion weighted imaging (DWI) and a battery of language assessments including the Boston Naming Test (BNT), the Peabody Picture Vocabulary Test (PPVT), the Controlled Oral Word Association Test (COWAT), Semantic Fluency Test (SFT), and a subset of the Boston Diagnostic Aphasia Examination (BDAE). Results were considered significant for p<0.05, corrected for multiple comparisons with cluster-wise family-wise error rate. We found a diffuse linear decrease with age in global white matter fractional anisotropy (FA) and a significant focal increase in FA in the superior cerebellar peduncle. Increased BNT scores were associated with increased FA in the left SLF, and in the posterior and anterio-lateral portions of the right IFOF. Increased SFT and PPVT scores were associated with increased FA in the posterior portion of the right IFOF. Decreased FA in the body of the corpus callosum (left) was associated with higher COWAT scores. We found no association between FA and BDAE scores. Our data show, as expected, global decreases in white matter structural integrity with age. In addition, we found that FA decreases faster with age in the right superior longitudinal fasciculus in males compared to females. However, a positive correlation between increased FA and language testing scores in multiple regions of the non-dominant IFOF indicates that more robust language networks with bilateral structural connectivity may contribute to better overall language functioning, regardless of age.